Representations of Afghans in the Iranian Cinema - Jauhiainen, Jussi S.; Eyvazlu, Davood (SAGE Publications, 2026)
This article explores the shifting cinematic representation of Afghans in Iranian fiction films from the 1980s to the mid-2020s, focusing on their social, spatial, and gendered positioning. Drawing on geocritical, feminist, and postcolonial frameworks, it conducts qualitative content analysis of 34 key films to trace how portrayals of Afghans evolved in relation to Iranian state policies and societal attitudes toward Afghans in Iran. Early cinematic depictions largely confined Afghans, in this case, all men, to marginal rural or suburban spaces in Iran, portraying them as undocumented laborers with limited agency, while Afghan women were strikingly absent. As national policies moved from a posture of welcome to repatriation and, more recently, partial integration, filmic narratives shifted. Afghans increasingly appeared in films in urban, domestic, and public settings, with more nuanced representations of gender and generational experiences. Since the 2010s, Afghan women have gained visibility in selected Iranian films as complex figures challenging both Iranian and Afghan patriarchal norms. Post-2015 films also explore aspirations and mobility of second- and third-generation Afghans—toward Europe or back to Afghanistan—revealing imaginaries of identity and belonging. Cinematic developments reflect broader socio-political transformations and contribute to public discourse on immigration, integration, and social change in contemporary Iran.